(untitled) (International Journal of Engineering and Computer Science, 2017)
Vehicular Ad Hoc Network (VANET) is a subgroup of mobile ad hoc network (MANET). It is an emerging new technology to exchange information between vehicles to vehicles. VANETs are considered as one of the most noticeable technologies for improving the efficiency and safety of transportation systems. VANET mainly used to exchange traffic information between the vehicles and prevent accident. In VANETs the high mobility of the nodes is the major concern. This dynamic topology makes the route unstable and unreliable for exchange of information or messages among the vehicles in the ad hoc network. To improve the throughput and performance of the VANETs, routes between nodes must be reliable, less overhead and stable. It is a challenging task to design a routing protocols for VANETs which should support the intelligent transportation system (ITS) for enhancing the driver’s safety, improving whole driver experience and regulating traffic. In this paper, the various challenges and issues of routing protocols of VANETs are discussed about its advantages and disadvantages in VANETs scenarios.